Functionalized liposomes as drug nanocarriers for active targeted cancer therapy: a systematic review. (3rd April 2022) - Abbasi, Hanieh; Rahbar, Nadereh; Kouchak, Maryam; Khalil Dezfuli, Parna; Handali, Somayeh
Abstract: Cancer is a broad term used to describe a group of diseases that have more than 270 types. Today, due to the suffering of patients from the side effects of existing methods in the treatment of cancer such as chemotherapy and radiotherapy, the employment of targeted methods in the treatment of this disease has been received much consideration. In recent years, nanoparticles have revolutionized in the treatment of many diseases such as cancer. Among these nanoparticles, liposomes are more considerable. Active targeted liposomes show an important role in the selective action of the drug on cancer cells. Until now, a variety of anti-cancer agents have been reported for targeted delivery to cancer cells using liposomes. The results of in vitro and studies in vivo have been shown that selective action of the targeted liposomes is increased with reduced side effects and toxicity compared with free drugs or non-targeted liposomes. This systematic review expresses the reports of this type of drug delivery system. Search terms were searched through several online databases including PubMed, Scopus, and Science Direct from 1990 to 2019 and the quality evaluation was performed. Out of 11, 676 published articles, 196 articles met the inclusion criteria. The current report reviews developments in the liposomes targeted with aptamer, transferrin, folate, and monoclonal antibodies.